Roland Mellor, Tacitus, New York-London, Routledge, 1993, XII + 212 pp. ISBN 0-415-90665-2 (Minerva. Revista de Filología Clásica, 2019)
Reseña de Roland Mellor, Tacitus, New York-London, Routledge, 1993, XII + 212 pp. ISBN 0-415-90665-2